Secondary prevention through comprehensive cardiovascular rehabilitation: From knowledge to implementation. 2020 update. A position paper from the Secondary Prevention and Rehabilitation Section of the European Association of Preventive Cardiology. (7th April 2020) - Ambrosetti, Marco; Abreu, Ana; Corrà, Ugo; Davos, Constantinos H; Hansen, Dominique; Frederix, Ines; Iliou, Marie C; Pedretti, Roberto F E; Schmid, Jean-Paul; Vigorito, Carlo; Voller, Heinz; Wilhelm, Matthias; et al.
Abstract: Secondary prevention through comprehensive cardiac rehabilitation has been recognized as the most cost-effective intervention to ensure favourable outcomes across a wide spectrum of cardiovascular disease, reducing cardiovascular mortality, morbidity and disability, and to increase quality of life. The delivery of a comprehensive and 'modern' cardiac rehabilitation programme is mandatory both in the residential and the out-patient setting to ensure expected outcomes. The present position paper aims to update the practical recommendations on the core components and goals of cardiac rehabilitation intervention in different cardiovascular conditions, in order to assist the whole cardiac rehabilitation staff in the design and development of the programmes, and to support healthcare providers, insurers, policy makers and patients in the recognition of the positive nature of cardiac rehabilitation. Starting from the previous position paper published in 2010, this updated document maintains a disease-oriented approach, presenting both well-established and more controversial aspects. Particularly for implementation of the exercise programme, advances in different training modalities were added and new challenging populations were considered. A general table applicable to all cardiovascular conditions and specific tables for each clinical condition have been created for routine practice.